(untitled) (Tribhuvan University Journal of Microbiology, 2025)
Objective: To assess antibiotic resistance in Escherichia coli isolated from chicken droppings from selected poultry farms within Kathmandu valley. Methods: Stool samples of chicken from 21 different farms were collected aseptically and transported to Central Department of Microbiology laboratory. Samples were cultured in MacConkey and M-Endo agar to isolate E. coli and was confirmed phenotypically using biochemical tests. The isolates were tested for antimicrobial susceptibility by modified Kirby-Bauer disk diffusion method following CLSI guidelines. Results: E. coli were isolated from all 104 dropping samples. E. coli isolates were resistant to ampicillin/sulbactam (91.34%), cefoxitin (98.07%), chloramphenicol (77.88%), ciprofloxacin (83.65%), contrimoxazole (79.81%), gentamicin (65.38%), levofloxacin (83.65%), and tetracycline (100%). While less proportions of E. coli were resistant to ceftriaxone (16.35%), colistin (3.85%) and imipenem (25%). Out of 104 isolates, 94 (90.38%) were multidrug resistant (MDR). Frequency of cleaning of the coop (p = 0.0017), farm size (p <0.001), farm operation (p<0.001), water source (p < 0.001) and common diseases of poultry (p < 0.001) were found significantly associated with MDR E. coli. Conclusion: High prevalence of MDR E. coli was found on chicken within Kathmandu valley, which might be introduced into humans through food chain. Therefore, adherence of biosecurity measures for reducing the use of antibiotics in the poultry farms is suggested.